Effect of bauxite additives on ash sintering characteristics during the K2CO3-catalyzed steam gasification of lignite. Issue 9 (23rd December 2014) - Zhang, Jiguang; Zhang, Li; Yang, Zhongqing; Yan, Yunfei; Mao, Yandong; Bi, Jicheng
Abstract : We report here the ash sintering characteristics of LLI lignite with added bauxite during K2 CO3 -catalyzed steam gasification. Abstract : We report here the ash sintering characteristics of LLI lignite with added bauxite during K2 CO3 -catalyzed steam gasification. The ash samples were prepared using a catalytic gasification system at 1123 K under a steam atmosphere with a carrier gas of N2 . The ash sintering temperature was determined using a pressure-drop sintering device in inert N2 . The ash mineralogy and morphology were determined by X-ray diffraction and energy-dispersive X-ray spectrometry-scanning electron microscopy. The K2 CO3 catalyst decreased the sintering temperature of the ash samples and increased the amount of melting of the ash. The presence of kaliophilite facilitated the formation of the liquid phases and triggered the start of sintering, resulting in a lower ash sintering temperature. The addition of bauxite reduced the degree of melting of the ash and led to a higher ash sintering temperature. The main reason for this is that bauxite containing sufficient SiO2 and Al2 O3 reacts with other minerals to generate more refractory silicon oxide and decreases the amount of arcanite (which acts a flux) and amorphous material in the ash. The addition of bauxite also decreased the rate of gasification of lignite by reacting with K to generate water-insoluble kaliophilite, which deactivated the K catalyst.